Edukasi Tentang Manfaat Imunisasi Lengkap Dan Polio Bagi Anak Di Desa Padang Balua - Andin; Rice Mandowa (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Immunization is one of the preventions by using weakened germs or products that are then inserted into the body to obtain immunity against infectious diseases according to the product. Non-compliance with immunization can affect the source of disease transmission. Infectious diseases are a major problem in increasing morbidity and mortality rates in children. Low non-compliance with immunization in children results in children growing up in an unhealthy state. Factors that influence the occurrence of incomplete immunization due to the perception of parents that immunization is not necessary because it can cause children to become sick and less intelligent. The perception that arises in the community, especially mothers, can occur because of the lack of knowledge and attitudes related to immunization. In fact, the immunization program has shown effectiveness in preventing infectious diseases. The success of the immunization program cannot be separated from the knowledge and attitudes of mothers in immunizing their children. One of the effective interventions in increasing knowledge and attitudes is education. Education on immunization compliance like this is attempted to be an ongoing activity so that it can increase community immunization related to knowledge and attitudes in providing child immunization. The outcome of this program can be achieved according to national targets. In addition, compliance with immunization can save costs in preventing certain diseases.